PEMBELAJARAN BERBASIS KOMPUTE - Sarjiati Sarjiati (Al-Misbah (Jurnal Islamic Studies), 2013)
In this global era , the more rapid development of science , which is characterized by the rapid advancement of information and communication technology world , encourage changes in education. Teachers (educators) are no longer present as the sole source of knowledge in a learning process . Therefore , an educator (teacher) if you want to keep survive in playing its role in the process of learning activities , they should have the creativity , in making the changes (innovations) , approaches , methods in the process of teaching and learning activities . In order to facilitate this learning , then teachers (educators) need to have a creative and innovative spirit . Therefore , a teacher is not enough just to master the competency (cognitive) alone, but also have to master information technology as a medium of communication , computer-based learning interesting and fun